Female attitudes and attitude change toward males and females, following exposure to soft-core pornography, varying in levels of aggression. - Gil Socorro, Africa (2019)
Consumption and distribution of pornographic material is vast and a cross-cultural phenomenon. The exploration of the effects of pornography on attitudes has revealed that this material causes a range of effects amongst its male consumers, including stereotypical sex-role beliefs, anti-women thought and adherence to rape myths. This paper used a classic pre-posttest design to elucidate what effects this material has on female participants (N= 242). Through the use of the Attitudes towards Women Scale and the Attitudes toward Men scale it was found that females did not experience significant attitude changes towards other females, upon exposure. However, they do show changes in their hostile male beliefs for clips depicting sexual aggression, and benevolent beliefs for clips depicting a flirtatious interaction, a romantic erotic scene, and, for a scene depicting rape. These findings are reviewed and discussed in light of the Gender-Schema Theory, Sexual Objectification Theory and Empathetic Viewer Theory.